2023
DOI: 10.37040/geografie.2023.007
|View full text |Cite
|
Sign up to set email alerts
|

Trends of hydroclimatic variables and outflow in the Athabasca River basin

Abstract: Our study focuses on assessing trends of hydroclimatic variables and their impact on the runoff regime in the Athabasca River basin in two periods (from the beginning of monitoring until 2011 and 1971−2011). Applied methods included the Mann-Kendall statistical test, linear regression, multiplicative decomposition of data series, the Indicators of Hydrologic Alteration, and the Range of Variability Approach. Temperature records indicated a strong regional warming trend, which influenced decreased snowfall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Due to climate changes recently, many of the time series homogeneity studies point to a change in the annual discharge regime in the early 1980s in different basins in Croatia. Moreover, studies confirmed the interruption of homogeneity in the early 1980s in air pressure, precipitation, surface runoff, and a time series of differences between rainfall amounts and potential evapotranspiration [18,31,32].…”
Section: Discussionmentioning
confidence: 58%
“…Due to climate changes recently, many of the time series homogeneity studies point to a change in the annual discharge regime in the early 1980s in different basins in Croatia. Moreover, studies confirmed the interruption of homogeneity in the early 1980s in air pressure, precipitation, surface runoff, and a time series of differences between rainfall amounts and potential evapotranspiration [18,31,32].…”
Section: Discussionmentioning
confidence: 58%